ANALISIS POTENSI WILAYAH BERBASIS KOMODITAS PERTANIAN TANAMAN PANGAN SERTA KONTRIBUSINYA TERHADAP PEREKONOMIAN KABUPATEN BONDOWOSO - Siti Qomariyah; Mustapit mustapit; Agus Supriono (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2018)
Bondowoso regency is one of the regencies in East Java Province which regional economic growth is relatively unprogressive. The main supporters of Bondowoso Regency's economic growth are agriculture, forestry and fishery sectors. This study aims at 1) to determine the kind of crops in each district in Bondowoso area. 2) to know the potential crops in Bondowoso, 3) To count the crops contribution to the economical sector in Bondowoso 4) To know the economic supporting system in Bondowoso. The method used in this study is analytic. This study also uses the document. The analysis method used is LQ analysis, the strength criteria of LQ,proportion formula, and scalogram analysis. The findings show that ; 1) each district has different comodity result, but the comodity of crops including rice and corn are principally identified in most of Bondowoso area, 2) The comodity such as rice is relatively potential to stand In Bondowoso, 3) the contribution of rice is high, 4) Mostly the districts in Bondowoso area have a good supporting system to stand the potential of crops comodity.